Memanfaatkan Sistem Pakar untuk Membantu Analisa Diagnosa Penyakit Obstetri dan Ginekologi - I Gede Susrama (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Too many problems of the death rate caused by the birth. First, it is caused by the less information aboutthe obstetry health and ginekology. The second is, the women still feel ashame to consult directly to the doctorabout their private health, it is why, because most of the obstetry and the ginekology doctor are men. And thethird is, there are too many people think that the health problems can be solved by the traditional way which isuncertain to able to diagnose the body condition. So, waiting untill the condition become worse, they are visitingthe specialist doctor. To solve those problems, it is built an intelligent system program that can be used fordiagnosing the disease, especially for the women health. Intelligent system is a computer software based onknowledge for the certain domain and using the inference reasoning similar to a human intellectual for solvingthe problems. Intelligent system will identify a kind of the disease to log the indication. This intelligent system isexpected to help and give the preventive suggestion and the medical treatment.Keywords: Intelligent system, Obstetry, Ginekology, Women